(untitled) - Tinsley Keeton, William (New York, 1993)
An introductory biology text for undergraduate students, this book has now been updated for its fifth edition. It takes an integrated approach and, for each revision, new developments in biology are incorporated into the fabric of the text. Major parts of the text have now been reorganized and a wide range of ancillaries plus current research and information are included.
Keywords: Biology,Sinh học